THE INFLUENCE OF ISLAMIC GOLDEN AGE ON MODERN SCIENTIFIC THOUGHT: A COMPREHENSIVE LIBRARY RESEARCH - Riyawi, Mohd. Rafi; Sutarmo, Sutarmo (State Islamic University of Sultan Syarif Kasim Riau, 2025)
The Islamic Golden Age, spanning approximately from the eighth to the fourteenth century, was a period of remarkable intellectual and scientific achievement that played a significant role in shaping the foundations of modern science. This study aims to examine the major contributions of Muslim scholars across key disciplines, including mathematics, astronomy, medicine, chemistry, and philosophy, and to analyze their influence on the development of modern scientific thought and methodology. Particular attention is given to the emergence of empirical observation and experimentation, most notably in the works of Ibn al-Haytham (Alhazen), whose methodological approach laid important foundations for the modern scientific method. The study highlights seminal contributions such as algebra developed by Al-Khwarizmi, advances in optics by Ibn al-Haytham, and medical innovations by Ibn Sina (Avicenna) and Al-Razi (Rhazes), all of which significantly advanced scientific knowledge. Furthermore, the paper examines the role of the translation movement, through which Islamic scientific texts were transmitted into Latin, facilitating the flow of knowledge to Europe and contributing to the intellectual developments of the Renaissance and the Scientific Revolution. Finally, this study explores the enduring impact of Islamic scholarship on contemporary scientific approaches, technological development, and educational practices, underscoring the lasting legacy of the Islamic Golden Age in modern science and technology.